DURUUSU AL-LUGHAH AL-ARABIYAH AL-JUZ AL-AWWAL FII TATWIIRI TA’LIIMI AL-LUGHAH AL-ARABIYAH - Anyes Latifatul Insaniyah; M. Nailul Hamam (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
Textbooks are all forms of material used to assist teachers in carrying out teaching and learning activities in class. Educational material is the most important thing in the teaching and learning process and is a factor that affects the quality of education. The text book